2001
DOI: 10.1111/j.1471-0528.2001.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory responses to maternal hyperoxaemia and hypoxaemia assessed non‐invasively in fetal sheep at 0.3–0.5 gestation in acute experiments

Abstract: Maternal hypoxaemia in early pregnancy causes similar fetal circulatory responses to those in late pregnancy: bradycardia, reduced venous flow velocities, augmented pulsatility in veins and a redistributional flow velocity pattern of the umbilical and common carotid arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Our finding is in agreement with published experimental studies (13,22). It has been shown that a comparable degree of fetal hypoxemia with our study caused a profound and immediate distension of the DV inlet (14,22).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our finding is in agreement with published experimental studies (13,22). It has been shown that a comparable degree of fetal hypoxemia with our study caused a profound and immediate distension of the DV inlet (14,22).…”
Section: Discussionsupporting
confidence: 94%
“…Hypoxemia leads to the dilatation of DV and an increase in the volume blood flow shunting through it (14,20). Studies on fetal sheep in early pregnancy have shown increased pulsatility in DV blood velocity waveform pattern during hypoxemia (13). Another mechanistic pathway leading to increased pulsatility in Doppler-derived DV blood velocity waveform can be a rise in end-diastolic pressure of the ventricles (11).…”
mentioning
confidence: 99%
“…The novel finding, on scanning electron microscopy, of longitudinal corrugations on the endothelial surface of the ductus venosus may have functional relevance. The hourglass shape, endothelial corrugations and the elastin-rich adventitia may assist in the process of dilatation of the ductus venosus 1,2 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, animal studies have demonstrated that the ductus venosus diameter increases in response to fetal hypoxemia, enhancing the shunting of oxygenated blood 1,2 . There is, however, conflicting evidence from previous studies about the structure of the ductus venosus, especially with regard to the presence of a sphincter at the ductus venosus inlet [9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation